سيميائية العتبات النصية لرواية "دفاتر الورّاق" " لجلال برجس - غربي, غالية; حلواجي, دنيا; عطيا الله, وفاء (جامعة الوادي - University of Eloued, 2023)
الملخص: تعتبر العتبات النصية مادة مهمة وثرية ،اهتمت السيميائية بدراستها، وذلك لما تشكله من أهمية وحضور فعال في النص من أجل عن البنى العميقة في النص الإبداعي ،كما أنها استطاعت أن تكون موضوعا للدراسة النقدية في الساحة الأدبية . في بحثنا هذا الموسوم ب:سيميائية العتبات النصية لرواية دفاتر الوراق لجلال برجس ،والذي حاولنا من خلاله التعرف على هذه العتبات والولوج إلى عالم النص وذلك من خلال دراسة مكونات السيميائية المتمثلة في :العنوان، الاهداء، الصورة، الالوان، العناوين الداخلية، والتي ساهمت في إمكانية قراءة وفهم النص واستيعابه والإحاطة به من جميع جوانبه الداخلية والخارجية. في الاخير نستخلص من خلال دراستنا أن العتبات النصية لها دور بارز في دراسة النصوص الأدبية انطلاقا من السيميائية التي وضعتنا أمام تحديات تسعى في اعماقها للوصول إلى دلالات النص لكل من التراكيب البنائية وكشف جماليات النص الأدبي. Abstracts : Summary : Textual thresholds are considered an important and rich material, which semiotics focused on studying, due to its importance and effective presence in the text in order to reveal the deep structures in the creative text, and it was also able to be a subject of critical study in the literary arena. In our research, which is tagged with: the semiotics of the textual thresholds of the novel Dafater al-Warraq by Jalal Barjas, through which we tried to identify these thresholds and access the world of the text by studying the components of semiotics represented in: title, dedication, image, colors, internal titles, which contributed to The ability to read and understand the text, assimilate it and take note of it in all its internal and external aspects. In the end, we conclude through our study that the textual thresholds have a prominent role in the study of literary texts based on semiotics, which put us in front of challenges that seek in its depths to reach the semantics of the text for each of the structural structures and revealing the aesthetics of the literary text.
Keywords: semiotics, textual thresholds, novel.; سيميائية، العتبات النصية، الرواية